IDEOLOGICAL BIASES IN THE QURANIC EXEGESIS:: Nawawi al-Bantani and Muhammad Uthaimin’s Views on Heresy (TAJDID: Jurnal Ilmu Ushuluddin, 2022)
This paper aims to figure out Nawawi al-Bantani and Muhammad al-‘Uthaimin about the heresy verses in the Qur’an. This research stems from the problem of the scholar’s views and responses to the traditions that are considered heretical. From this controversy, this article attempts to analyze the meaning of heresy in Nawawi’s interpretation of Marāḥ Labīd and Muhammad al-‘Uthaimin’s interpretation of the Tafsīr Qur’ān al-Karīm. These two works of interpretation represent two different religious schools and regions. By using descriptive-analytical and comparative methods, this study produced two findings, 1) the mazhabiyyah paradigm adopted by the mufassir greatly influenced the results of tafsir; 2) despite using the same method of monitoring the Qur’an, both Nawawi al-Bantani and Muhammad al-‘Uthaimin made different restrictions because of their ideological influence. The results of this study also show that Nawawi al-Bantani in the interpretation of Marāḥ Labīd and the control of Muhammad al-‘Uthaimin in the interpretation of the Qur’an al-Karim about heresy in the Qur’an have different connotations. From the socio-historical context, the resources, methods, and styles used to have a significant influence so as to produce differences and similarities in the verse about heresy. The position of this research is the finding of Afif Suaidi (2021) regarding ideological tendencies in transliterating the Koran that the variety and translation of the Koran is caused by the religious understanding adopted by the author and aims to support ideology in its interpretation. Tulisan ini bertujuan mengkaji penafsiran Nawawi al-Bantani dan Muhammad al-‘Utsaimin tentang ayat-ayat bid’ah. Penelitian ini berangkat dari perdebatan para ulama’ tentang sikap dan respon mereka terhadap sejumlah tradisi yang dianggap bid’ah. Berangkat dari kontroversi tersebut, artikel ini berusaha menganalisis makna bid’ah dalam tafsir Marāḥ Labīd karya Nawawi dan Tafsīr al-Qur’ān al-Karīm karya Muhammad al-‘Uthaimin. Dua karya tafsir ini merepresentasikan dua aliran keagamaan dan kawasan yang berbeda. Dengan menggunakan deskriprif-analitis dan metode komparatif, penelitian ini menghasilkan dua temuan, 1) bahwa paradigma mazhabiyyah yang dianut oleh mufassir sangat mempengaruhi pada hasil penafsirannya; 2)  meski menggunakan metode yang sama dalam menafsirkan al-Qur’an, baik Nawawi al-Bantani dan Muhammad al-‘Uthaimin mengasilkan penafsiran yang berbeda karena dipengaruhi ideologinya. Hasil penelitian ini juga menunjukkan bahwa penafsiran Nawawi al-Bantani dalam tafsir Marāḥ Labīd dan penafsiran Muhammad al-‘Uthaimin dalam Tafsīr al-Qur’ān al-Karīm tentang bid’ah dalam al-Qur’an memiliki konotasi yang berbeda. Dari konteks sosio-historis, sumber penafsiran, metode, dan corak yang digunakan memberikan pengaruh signifikan sehingga menghasilkan perbedaan serta persamaan dalam penafsiran ayat tentang bid’ah. Posisi penelitian ini adalah menegaskan temuan Afif Suaidi dkk (2021) tentang tendensi ideologis dalam transliterasi al-Qur’an bahwa ragam penafsiran maupun terjemahan atas al-Qur’an disebabkan oleh pemahaman keagamaan yang dianut penulisnya dan bertujuan mempromosikan ideologi tertentu dalam tafsirnya.